Investigation into Translation Strategies for Culture-Loaded Terms: A Case Study of the English Translation of Frog - Wang, Haibo (International Theory and Practice in Humanities and Social Sciences, 2025)
Background: Mo Yan’s works have garnered considerable influence in English-speaking countries, with the translator Howard Goldblatt playing a pivotal role in their dissemination and reception. Goldblatt’s English translation of Mo Yan’s Frog, published in 2014, received widespread recognition and praise. The original text contains numerous culture-loaded terms symbolizing traditional Chinese culture, posing significant challenges for the translator. However, it is precisely these elements that contribute to the work’s enduring appeal. Methodology: Based on the framework of Nida’s classification of cultural concepts, the study mainly employs the qualitative methodology of parallel text analysis to examine Goldblatt’s translation strategies and their effectiveness in rendering the culture-loaded terms in Frog. Findings: The study indicates that to convey the cultural richness of the source text while ensuring readability and acceptability for the target readers, Goldblatt employed different strategies based on the nature of the terms. For terms with close or direct English equivalents, the translator opted for domestication. In contrast, particularly for linguistic culture-loaded terms, he frequently used literal translation or transliteration. However, when terms with rich cultural connotation might confuse English-speaking readers, Goldblatt resorted to domestication accompanied by direct explanations to provide readers with contextual understanding. Conclusion: The study concludes that translators must thoroughly understand the target readers’ expectations. Translators should strike a balance between creativity and fidelity to the source text. While remaining faithful to the original’s ideas and style, they may appropriately adjust their translation strategies to align with the comprehension level and reading preferences of target readers.